Identity, Beliefs, and Political Conflict - Nicola Gennaioli; Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2019)
We present a theory of identity politics that builds on two ideas. First, voters identify with the social group whose interests are closest to theirs and that features the strongest policy conflict with outgroups. Second, identification causes voters to slant their beliefs of self and others toward group stereotypes. The theory yields two main implications: i) voters' beliefs are polarized along the distinctive features of salient groups; ii) economic shocks that render new groups salient bring about large and non standard changes in beliefs and policies across many issues. In particular, exposure to globalization or cultural changes may induce voters to switch identities, dampening their demand for redistribution and exacerbating conflicts in other social dimensions. We show that survey evidence is broadly consistent with these implications.
Keywords: H00; Z10; 330